Police officer's DNA on crime scene samples – Indirect transfer as a source of contamination and its database-assisted detection in Austria. (December 2017) - Neuhuber, Franz; Kreindl, Gabriele; Kastinger, Tamara; Dunkelmann, Bettina; Zahrer, Waltraud; Cemper-Kiesslich, Jan; Grießner, Ines
Abstract: The capability of nowadays used forensic DNA analysis techniques to generate DNA profiles out of evidence samples that contain only a low amount of biological material has also enhanced the chance to detect contamination incidents. The identification of such contamination events to reduce false positive results and to avoid misguiding investigations still represents a challenge for forensic laboratories. With improved methods to detect contamination incidents it becomes apparent that indirect transfer of biological material during crime scene investigation is a serious issue. By presenting different cases of indirect transfer of biological material from police officers during crime scene investigation we would like to highlight the benefits of a Police Elimination Database (PED) for database-assisted detection of contamination incidents.